FAKTOR - FAKTOR YANG MEMPENGARUHI PRILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN DI PERCETAKAN ADHYA MULTI SUKSES - Munthe, Richa Afriana (Eko dan Bisnis: Riau Economic and Business Review, 2019)
The development of business and technology in the current era of globalization is growing rapidly and is characterized by a level of competition between companies that is getting higher and tougher. With current technological developments have changed the pattern of human work to be increasingly fast, effective and efficient in doing a job, especially in data processing. So there needs to be an adjustment between work patterns with technological developments. The purpose of this study was to determine the factors that influence consumer behavior in purchasing decisions at Adhya Multi Sukses printing. The population in this subject are consumers who have made purchases at the Adhya Multi Sukses Printing in 2017. The sampling technique in this study is to use simple random sampling, which is a method of sampling non probalities by simple random methods and each respondent has the same possibility of being selected as a respondent. To determine the number of samples using the Slovin formula, 95 samples were obtained from a population of 1,845 people. The results showed that the product, price, promotion, and distribution channels affected the purchasing decisions at Adhya Multi Sukses printing